KEHIDUPAN MAHASISWA UNIVERSITAS GADJAH MADA DI LINGKUNGAN KERATON YOGYAKARTA 1949-1970-an - , ARIF BINTORO, Dr. Mutiah Amini, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study focus on the students life of Gadjah Mada University in Keraton neighborhood of Yogyakarta 1949-1970s. In the early establishment, Gadjah Mada University owned no adequate lecture buildings. Of the Sultan Hamengku Buwono IX official permit, Gadjah Mada University got permission to using some places in the Keraton neighborhood of Yogyakarta. Gadjah Mada University was born during Revolution Physic and itâs became Indonesian struggle symbol. The limits of facilities to study did not put intention down for the scholars studying in Gadjah Mada University. Itâs not just feels in studying activities, but its also in students life are became in the limits of condition. This process of writing committed by using historical methods with application from both primary or secondary sources. Oral history generates alternative ways to explore more relevant information when textual sources are inaccessible. In the sense of historiography, this research is intended to contribute relevant reference regarding to students life of Gadjah Mada University. Gadjah Mada University and scholars who lived around Keraton Yogyakarta caused interrelation with the close people. It brings about mutual relationship within both sides, directly, and indirectly.